Corrigendum to “Properties, performance and associated hazards of state-of-the-art durable water repellent (DWR) chemistry for textile finishing” [Environ. Int. 91 (2016) 251–264]:(Preliminary screening of perfluorooctane sulfonate (PFOS) and other fluorochemicals in fish, birds and marine mammals from Greenland and the Faroe Islands (2005) 136(2) (323–329), (S0269749105000412), (10.1016/j.envpol.2004.12.020)) - Holmquist, H.; Schellenberger, S.; van der Veen, I.; Peters, G. M.; Leonards, P. E.G.; Cousins, I. T. (Environment International, 2020)
The authors regret that the chemical formula of perfluorooctanoic acid (PFOA) was not correct in Fig. S7 in the Supplementary material. The authors would like to apologise for any inconvenience caused.